Asuhan Keperawatan Pada Pasien Dengan Gastroenteritis Akut Di Ruang Interne Rsud Prof. H. Muhammad Yamin, S. H Pariaman - Adinda Cahayu Mulia Eliandya; Debby Silvia Dewi; Hilma Yessi; Mike Asmaria (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Acute gastroenteritis is an infectious disease that remains a global and national health problem caused by pathogenic microorganisms such as bacteria, viruses, or parasites that enter the digestive tract. Based on data from the World Health Organization (WHO) in 2024, the number of acute gastroenteritis cases reaches 1.7 billion each year. According to the Indonesian Ministry of Health, gastroenteritis is the second most common disease in Indonesia with around 2.2 million cases, while in West Sumatra there were 43,706 recorded cases. In Pariaman City, 1,325 cases were treated out of a target of 2,544. Medical record data at RSUD Prof. H. Muhammad Yamin, S.H. Pariaman showed that the number of patients with gastroenteritis in 2025 reached 219 cases. The purpose of this case study is to describe the application of nursing care for patients with acute gastroenteritis. The method used was a case study through observation and interviews conducted for 5 days, from February 11 to 15, 2026, in the Internal Medicine Ward of Prof. H. Muhammad Yamin Regional Public Hospital, S.H Pariaman, involving one patient with acute gastroenteritis. The results of the study identified six nursing problems: diarrhea, hypovolemia, acute pain, risk for ineffective peripheral perfusion, risk of infection, and risk of nutritional deficit, with diarrhea as the primary priority. Evaluation over five days of care showed that all nursing problems gradually improved and were resolved, allowing the patient to be discharged in a stable condition. Patients is expected to maintain a proper diet, food and environmental hygiene, as well as a healthy lifestyle.